Morality as a source of (banal) evil. Hannah Arendt reads Kant - Łojek, Stanisław (Hybris, 2013)
The experience of totalitarianism made Arendt notice how problematic the common understanding of morality is. If we identify it with the obedience to the rules governing human relationships it can happen that when those rules become questionable we are no longer able to distinguish right from wrong. But totalitarian leaders not only rejected the existing rules; they replaced them with the ones that prescribed evil things. Arendt thinks that the real moral problem is with those "ordinary" people who adapted to the new situation. Both the ease of their conversion and the example of those who were able to resist it, led her to conclude that “morality of rules” might be detrimental to the activities that can make us refrain from doing evil. Analyzing these activities, which are thinking and judging, Arendt often refers to Kant’s philosophy. I want to demonstrate the fruitfulness of this interpretation, and its importance to moral and political thought of Arendt herself. The presentation of these topics is supposed to deepen the reflection on the problem of "banal" evil.